(x,y,z)=(-4,-2,-5)
I added some images for explanation
Answer:
-6x (x + 1)(x - 1)
Explanation:
Before we begin, remember the following:
(-ve) * (-ve) = +ve
(-ve) * (+ve) = -ve
(+ve) * (+ve) = +ve
(+ve) * (-ve) = -ve
a² - b² = (a + b)(a - b)
Now, for the given:
(4x³ + 3x² - 6x) - (10x³ + 3x²)
First, we eill remove the brackets based on the rules mentioned above. This will give us:
4x³ + 3x² - 6x - 10x³ - 3x²
Now, we will combine like terms as follows:
(4-10)x³ + (3-3)x² - 6x
-6x³ - 6x
Taking -6x as a common factor:
-6x (x² - 1)
Factoring the bracket as difference between two squares will give us the final simplest form:
-6x (x + 1)(x - 1)
Hope this helps :)
Answer:
1 65/76
Step-by-step explanation:
To determine the number of modules that is in each story, we simply divide the number of modules by the number of stories.
= 140 / 14
Simplifying,
= 10 modules / story
Therefore, by even distribution we note that there are 10 modules per story.
<h2>Vertical distance gained from takeoff is 493.72 ft</h2>
Step-by-step explanation:
Refer the figure.
Horizontal distance = AB = 2800 ft
Angle = ∠B = 10°
We need to find AC that is h.
We have

Vertical distance gained from takeoff = 493.72 ft